Perbanyakan Tanaman Pulai Pandak (Rauwolfia serpentina L.) dengan Teknik Kultur Jaringan - Yunita, Rossa; Endang, Endang; Lestarai, Gati (Jurnal Natur Indonesia, 2011)
Due to over exploitation of its bark for medicinal herbs and made worse by problem in conventional breeding, Rauwolfia serpentina (Pulaipandak), has been considered rare and was currently reported to be an endangered species. Therefore, conservation measure is urgent to betaken. One of them is by in vitro propagation. In this research, in vitro propagation covers several activities, such as (1) shoot inductionwith the application of MS (Murashige and skoog) media enriched with ZPT 0.0; 0.1; 0.3 mg/l BAP combined with 0, 1, 2 mg/l 2ip, (2)shoot multiplication by using 0.0; 0.5; 1.0 mg/l BAP combined with 0.0; 0.1; 0.2 and 0.3 mg/l thidiazuron), (3) root induction IBA at theconcentration of 0.0; 0.5; 1.0; 1.5; 2.0; 2.5; 3.0 mg/l, and (4) acclimatization. The result showed that the best shoot induction for calli isthe in vitro stem by the application of MS + 0.3 mg/l BAP + 1 mg/l 2ip basic media. For shoot multiplication, the best media was MS + 0.5mg/l BAP + 0.1 mg/l ; while the best formula for root induction was MS + 1 mg/l IBA. The best media for plantlet acclimatization is compost+ soil mixture in 1:1 ratio.